Foreword - General Issue - Nick James (Legal Education Review, 2015)
This issue contains three papers first presented at a Legal Writing Symposium hosted by Melbourne Law School in December 2015. The event was designed to highlight the diversity of approaches to teaching legal analysis and writing in law school, and the creative and inspiring people who think deeply about these topics. When Kate Galloway, current Editor in Chief of the Legal Education Review, heard about the symposium she approached me to suggest a special edition to highlight the papers presented. This edition is the result of her creative suggestion, the generosity of the editors at the LER, and the commitment of the authors.